2022
DOI: 10.1038/s41598-022-19975-y
|View full text |Cite
|
Sign up to set email alerts
|

Bis-pharmacophore of cinnamaldehyde-clubbed thiosemicarbazones as potent carbonic anhydrase-II inhibitors

Abstract: Here, we report the synthesis, carbonic anhydrase-II (CA-II) inhibition and structure–activity relationship studies of cinnamaldehyde-clubbed thiosemicarbazones derivatives. The derivatives showed potent activities in the range of 10.3 ± 0.62–46.6 ± 0.62 µM. Among all the synthesized derivatives, compound 3n (IC50 = 10.3 ± 0.62 µM), 3g (IC50 = 12.1 ± 1.01 µM), and 3h (IC50 = 13.4 ± 0.52 µM) showed higher inhibitory activity as compared to the standard inhibitor, acetazolamide. Furthermore, molecular docking of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…hCA I, and hCA II; and AChE (Table 6). In the literature, Rasool et al [41] reported the synthesis of new thiosemicarbazones derived from 4-(dimethylamino)cinnamaldehyde which are powerful CA-II inhibitors. Additionally, molecular docking experiments were conducted to understand the atomic-level interactions of these derivatives.…”
Section: Metabolic Enzyme Inhibition Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…hCA I, and hCA II; and AChE (Table 6). In the literature, Rasool et al [41] reported the synthesis of new thiosemicarbazones derived from 4-(dimethylamino)cinnamaldehyde which are powerful CA-II inhibitors. Additionally, molecular docking experiments were conducted to understand the atomic-level interactions of these derivatives.…”
Section: Metabolic Enzyme Inhibition Propertiesmentioning
confidence: 99%
“…Experimental and theoretical Fourier transform infrared (FT-IR) values of the compounds (cm −1 ) a Theoretical13 C NMR data of the synthesized compounds, (δ/ppm)41/58.24 150.65 153.71 126.01/105.00 131.80 148.48 186.03 CH 3 :32.38 -63.44/58.24 150.67 153.50 126.01/104.90 131.80 148.34 184.69 CH 2 : 44.53 CH 3 : 13.84 -63.40/58.26 150.99 153.73 126.14/105.20 131.50 148.90 184.27 CH 2 : 51.66 CH═: 144.83 ═CH 2 : 122.94 -63.36/58.24 151.00 153.91 126.25/105.17 131.30 148.93 185.13 CH 2 : 5241/58.25 150.53 153.55 126.06/104.91 131.63 148.27 183.30 53.70, 32.0, 29.95, 24.08, 23.52, 22.67 (cyclohexyl carbons)…”
mentioning
confidence: 99%
“…Our ongoing research on discovering and developing new anticancer agents [39][40][41][42][43] is fueled by the exciting findings of coumarin derivatives with anticancer potential (as discussed previously). In this view, we present here design and synthesis of a novel series of molecular structures incorporating coumarin, pyrazole and thiazole rings in different configurations forms.…”
Section: Introductionmentioning
confidence: 99%
“…Research teams worldwide are currently dedicated to designing and developing novel categories of α-glucosidase inhibitors, with a particular emphasis on heterocycle-based α-glucosidase inhibitors that have garnered increased interest in recent years. [9][10][11][12][13][14][15][16][17][18] Various heterocyclic compounds have been found to show antidiabetic properties by acting as α-glucosidase inhibitors. [19][20][21][22][23] Chromone, known as a class of natural drugs, characterized by a benzoannelated γ-pyrone ring, exhibited the potential to behave as a privileged scaffold for the development of novel molecules in the development of new drugs.…”
Section: Introductionmentioning
confidence: 99%